2016
DOI: 10.1007/s13277-016-5421-3
|View full text |Cite
|
Sign up to set email alerts
|

FAT4 functions as a tumor suppressor in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer that is often associated with biologic behavior with frequent distant metastasis. FAT tumor suppressor homolog 4 (FAT4), a cadherin-related protein, is involved in a variety of biological processes as a tumor suppressor; however, the role of FAT4 in TNBC is still unclear. The aim of our study was to identify the role of FAT4 in TNBC and examine the underlying molecular mechanisms. The expression of FAT4 was evaluated by immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
6
18
0
1
Order By: Relevance
“…NF1 is a well-known tumor suppressor gene and it was mutated in 11% of the samples and ZFHX4 in 21% of the samples. We identified SNVs in the cadherin repeat domains of FAT family genes, i.e., FAT1 and FAT4 in 21% samples, which are functionally characterized as tumor suppressor genes in multiple cancers including ESCC (13,(32)(33)(34). In concordance with ESCC genomic profiles from Chinese and Japanese cohorts, we identified several previously reported recurrently mutated genes ( Supplementary Table 4).…”
Section: Somatic Mutation Spectrum Of Esophageal Squamous Cell Carcinomasupporting
confidence: 70%
“…NF1 is a well-known tumor suppressor gene and it was mutated in 11% of the samples and ZFHX4 in 21% of the samples. We identified SNVs in the cadherin repeat domains of FAT family genes, i.e., FAT1 and FAT4 in 21% samples, which are functionally characterized as tumor suppressor genes in multiple cancers including ESCC (13,(32)(33)(34). In concordance with ESCC genomic profiles from Chinese and Japanese cohorts, we identified several previously reported recurrently mutated genes ( Supplementary Table 4).…”
Section: Somatic Mutation Spectrum Of Esophageal Squamous Cell Carcinomasupporting
confidence: 70%
“…3d). These results are in agreement with a previous study in gastric and breast cancer cell lines [8,12], showing that silencing FAT4 expression increased invasion and migration of MDA-MB-436 and BT-549 breast Fig. 3 Functional role of FAT4 on cell proliferation, colony formation, and invasive ability.…”
Section: Discussionsupporting
confidence: 93%
“…FAT tumor suppressor homolog 4 (FAT4), is a member of the FAT family that consists of (FAT1-4) and encodes a single transmembrane protein containing 32-34 extracellular cadherin repeats, a transmembrane domain and a cytoplasmic domain [7]. FAT4 was identified as a tumor suppressor in mouse mammary epithelial cell line and triple-negative breast cancer [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of TUSC3 in cancer progression showed context-dependent manner in several solid tumors. TUSC3 was initially identified as a homozygous deleted gene in metastasized prostate cancer patients and its deficiency upregulated cancer progression and tumorigenesis in ovarian, prostate, glioblastoma and pancreatic cancers 20 24 . However, it has been also reported that TUSC3 was associated with genetic amplification or enhanced cancer progression in head and neck cancer and colorectal cancer 20 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%